KLASTERISASI DATA : ANALISIS KINERJA K-MEANS PADA SEKTOR PAJAK, EKSPOR, PERIKANAN, MODAL, DAN SUMBER DAYA - Achmad S.W.A Nurba; Dharma Fathahillah; Muhamad Shafly Pratama; Muhammad Rivaldi Bachtiar; Muhammad Chesta Adabi Putra; Sartika Lina Mulani Sitio (JRIS : Jurnal Rekayasa Informasi Swadharma, 2025)
This study aims to cluster Indonesian economic data patterns from five sectors: tax, export, fisheries, capital markets, and resources, using the K-Means algorithm. Data were obtained from BPS, the Ministry of Finance, the Ministry of Marine Affairs and Fisheries, the Financial Services Authority (OJK), and UN Comtrade. Pre-processing was carried out through data cleaning and normalization. The optimal number of clusters was determined using the elbow and silhouette methods. Clustering evaluation used Inertia, Silhouette score, and the Davies-Bouldin Index. The results show variations in cluster patterns in each sector, with the fisheries and capital markets sectors providing the best results (high silhouette scores). Visualization using PCA supports cluster interpretation. These findings demonstrate that K-Means is effective in economic data analysis and helps support more adaptive and data-driven policies.Penelitian ini bertujuan mengelompokkan pola data ekonomi Indonesia dari lima sektor: pajak, ekspor, perikanan, pasar modal, dan sumber daya, menggunakan algoritma K-Means. Data diperoleh dari BPS, Kementerian Keuangan, KKP, OJK, dan UN Comtrade. Pra-pemrosesan dilakukan melalui pembersihan dan normalisasi data. Jumlah klaster optimal ditentukan menggunakan metode elbow dan silhouette. Evaluasi klasterisasi menggunakan Inertia, Silhouette score, dan Davies-Bouldin Index. Hasil menunjukkan variasi pola klaster di tiap sektor, dengan sektor perikanan dan pasar modal memberikan hasil terbaik (silhouette score tinggi). Visualisasi menggunakan PCA mendukung interpretasi klaster. Temuan ini menunjukkan bahwa K-Means efektif dalam analisis data ekonomi dan bermanfaat untuk mendukung kebijakan yang lebih adaptif dan berbasis data.